Arthroscopic Decompression of a Type III Subspine Impingement - Víctor M. Ilizaliturri, Jr., M.D.; Rubén Arriaga Sánchez, M.D.; Carlos Suarez-Ahedo, M.D. (Arthroscopy Techniques, 2016)
Extra-articular hip impingement refers to a variety of hip disorders causing pain and limited function in young, non-arthritic patients. Recently, there has been an increased focus on analyzing the degree of anterior inferior iliac spine (AIIS) dysmorphism and its correlation with subspine impingement (SSI), defined as abutment between a prominent distal aspect of the AIIS and the anterior aspect of the femoral head-neck junction. Arthroscopic decompression of the AIIS is recognized as an effective treatment for SSI. However, there may be some inherent risks of performing this procedure arthroscopically that require further investigation.